PERSEPSI DAN KETAATAN UMAT ISLAM TERHADAP ULAMA - Iwan Zaenul Fuad; Agus Fakhrina; Abdul Aziz; A. Rosyid (JURNAL PENELITIAN, 2010)
People’s refusals and disobediences upon fatwa (released by MUI or ulama with their own opinions), followed by influence decreases of religious figures (ulama) towards Muslim community, were being such of phenomenal realities in Indonesia nowadays. This mass behavior might redefine their perceptions and thoughts about “the legitimate ulama”, according both; syara’ (religious legitimation), and social system. The research was located in Pekalongan Regency, thought-out known as “Kota Santri”, and plenty more, many Pesantren and Kyai have lived there. The result revealed that ulama and Muslim Community mostly had the same perception and view in understanding the meaning of Hadist “al-ulama’ waratsat al anbiya” (ulama are heir of prophets). Ulama’ as informants added ulama’ were religious successor leader after the end of Muhammad’s saw prophetic era. But, in another sides, there were some differences, especially in interpreting social label: Kyai, KH, or Ustadz. Muslim Community mostly thought that a person who had such social label was ulama. Meanwhile ulama noted Kyai, KH or Ustadz was just social label, no more. So, it seemed to be weird and screwy if we looked up the sosial fact of fidelity of Muslim Community in Pekalongan Residence. It also could be said that Muslim community in Pekalongan Residence were standing still their obidiece toward kyai, KH, Ustadz or another ones, not toward ulama yet.